Взаимодействия в системе алмаз–алмаз при огранке алмаза в бриллиант - Астапчик, С.А.; Кузей, А.М.; Зайцев, В.А. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2007)
The study has been made of the surface morphology of a diamond tool in the process of diamond faceting. It is established that the temperature increases up to 1275 K to 1350 K in a contact zone. The diamond wearing is shown to be associated with adhesion interaction between crystal surface and nickel-boron alloy as well as with abrasive action of diamond grains.